KARAKTERISTIK, MOTIVASI DAN KEPUASAN WISATAWAN ASAL INDONESIA YANG BERWISATA KE VIETNAM - Br Siregar, Kristina Valentina; Sasrawan Mananda, IGPB.; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
Vietnam has the inbound tourism growth in ASEAN within 20% and also Indonesian tourist visits to Vietnam increase every year. This study aims to identify the characteristics, motivation and satisfaction of Indonesian tourists who traveled to Vietnam and expected to be used as a consideration by tourism expertise, especially outbound tourism activities in order to fulfil their needs and expectations. The sample of this research is Indonesian tourists who have visited Vietnam. The sampling technique used purposive sampling method towards 100 respondents. Data collection techniques were conducted in several ways, such as: observation, questionnaires, literature study, and documentation. Data analysis was performed using quantitative descriptive analysis techniques. The results showed that the motivation of influencing most of Indonesian tourists who traveled to Vietnam was cultural motivation with an average value of 4.45 (strongly agree) and the indicator that had the highest value was seeing and knowing the culture in Vietnam with an average value. 4.53. In addition, in terms of the level of tourist satisfaction, it shows that among the four main components of tourism which consist of attraction, amenities, accessibility, and ancillary (4A), the attraction component has the highest satisfaction score of 87,1% (Very Satisfied) and the indicator with the highest score is Vietnam has a good and attractive natural tourism with total score of 88,8% (Very Satisfied). Overall, the satisfaction level of Indonesian tourists visiting Vietnam has score 80,7% (Satisfied), which means that Indonesian tourists visiting Vietnam are satisfied with attractions, amenities, accessibility, and ancillary in Vietnam.